The legacy of redlining and gentrification: Kansas City, Missouri - Pereyda, Nayelie Alexa (Kansas State University, 2022)
More Americans are moving back to urban areas, especially downtowns, more than ever before. Historically events and factors such as the Great Migration, white flight, racial covenants, and redlining have determined where people lived and have resulted in creating cities marked by segregation even today. Today, the U.S. is facing a housing affordability crisis affecting millions marked by the deterioration of existing homes; insufficient policies protecting tenants' rights; accountability of landlords and developers; existing federal programs and current budgets are not sufficient to meet the existing demands of the people. American cities today are struggling to address displacement due to gentrification as well as provide affordable and equitable housing. Gentrification leads to the displacement of many long-term residents due to rising home prices and rents, making it even more difficult for low and moderate-income residents. Like most cities in the US, Kansas City, Missouri (KCMO) is not unique when it comes to gentrification, displacement, and the affordable housing crisis. In this report, I explore if there is a connection between areas that have been historically redlined and areas that are gentrifying. I focus this study on Kansas City, Missouri, one of the largest metropolitan areas in Midwest US. In this study, I use map analysis to investigate the connections between redlining and gentrification in Kansas City, Missouri. Adapting the method developed by the Urban Displacement project to measure gentrification, I use ACS data and redlining maps of KCMO to find that there are some overlaps between historically redlined area and currently gentrifying areas. To understand anti-displacement policies and strategies, I utilize case studies from St. Louis, Missouri and Los Angeles, California. I use in-depth research and map analysis on KCMO and each case study are to make recommendations for future policies and ordinances within Kansas City targeting displacement. These recommendations include exploring possible funding sources outside the Housing Trust Fund, adopting explicit policies and zoning ordinances for anti-displacement, establish a housing demand model, and consider a tool or method to measure the effectiveness of policies and ordinances.
Keywords: Redlining; Gentrification; Displacement; Kansas City, Missouri